Competence, Self-Efficacy, And Work Discipline as Determinants of Employee Performance: Evidence From PT Rumah Desa Bali, Tabanan - Kadek Novi Natalia; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
Employee performance evaluation is essential for both organizations and employees, as it provides a basis for assessing work achievement, planning career development, and determining promotion opportunities. This study aims to examine the influence of competence, self-efficacy, and work discipline on employee performance at PT. Rumah Desa Bali, Tabanan. The population of this study consisted of all 33 employees of PT. Rumah Desa Bali. Since the population was relatively small, a saturated sampling technique was applied, in which all members of the population were included as research respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results of hypothesis testing show that competence has a positive and significant effect on employee performance. Self-efficacy also has a positive and significant effect on employee performance. In addition, work discipline has a positive and significant effect on employee performance. These findings indicate that improving employee competence, strengthening employees’ confidence in their abilities, and maintaining strong work discipline are important factors in enhancing employee performance at PT. Rumah Desa Bali.